High Subsidence Rate After Primary Total Hip Arthroplasty Using a Zweymüller-type Noncemented Implant With a Matte Surface. (7th June 2022) - Kawai, Toshiyuki; Goto, Koji; Kuroda, Yutaka; Okuzu, Yaichiro; Matsuda, Shuichi
Abstract : Introduction: The surface topography is one key factor that affects the initial fixation of prosthesis in total hip arthroplasty (THA). We aimed to evaluate the mid-term results of a Zweymüller-type noncemented femoral implant (Elance stem) that had a matte surface with a target average roughness of 1.0 to 2.5 μm. The prosthesis was subjected to alkali and heat treatments to enhance its bone-bonding property. Methods: In this retrospective study, 30 THAs (27 patients) done using an Elance stem from September 2012 to October 2014 were evaluated clinically and radiographically for a mean follow-up of 6.3 ± 1.7 years after the index THA. Results: Stem revision was indicated for six hips (20%). The survival rate with stem revision for any reason was 86.4% (95% confidence interval, 68.9%-94.8%) at 5 years. Stem subsidence >5 mm was noted in 17 hips (56.7%). The survival rate with stem subsidence >5 mm as the end point was 46.6% (95% confidence interval, 29.9%-64.2%) at 5 years. Conclusion: The Zweymüller-type noncemented stem with a low-roughness matte surface demonstrated a high subsidence rate, although the bone-bonding property was potentially enhanced by the alkali and heat treatments. Surgeons should be aware that an insufficient surface roughness could lead to poor mechanical fixation of the noncemented stem, even with an appropriate stem geometry and surface chemistry.